LONELY LENNIE IN JOHN STEINBECK'S OF MICE AND MEN - Elfath Akdawidjaja; Angelika Riyandari; Maria Sri Suryaningsih M.A (Celt: A Journal of Culture, English Language Teaching & Literature, 2008)
Loneliness is an emotional state when an individual finds him herself lack of qualitative interaction with other people. It does not only occur by the absence of other people around. but it also occurs with the presence of the others. The case study of Lennie Small provides A descriptive illustration of loneliness as the discussion reveals that Lennie suffers from psychological and cognitive loneliness. The feeling of loneliness itself is caused by being unable to fit in and being abused and rejected by others. The study also reveals how Lennie attempts to cope with loneliness through the desire for someone and by crying.